Well-Posedness For Generalized Equilibrium Problems With Βh-Monotone Trifunction - et. al., Wijdan S. Abed, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of this paper is to establish the existence and uniqueness of solutions of well-posedness for in connection with βh-monotone trifunction. To this aim, we deal with a subset A of Banach space V. A useful characterization of metric projection and sufficient conditions for these types of well-posedness are derived. Finally, the discussion provided by this paper can be used to prove that the concept of well-posedness for is equivalent to the existence and uniqueness of its solution.